Endovascular treatment for basilar artery occlusion: whether the “weekend effect” affects time metrics and clinical outcomes at a comprehensive stroke center - Bao, Jianying; Shen, Guangchen; Shi, Haibin; Lin, Zheng; Liu, Sheng (Frontiers in Neurology, 2024)
Objectives: To evaluate whether "weekend effect" would affect the time metrics and prognosis of acute ischemic stroke (AIS) patients who underwent endovascular treatment (EVT) due to basilar artery occlusion (BAO).Methods: Clinical data of AIS patients who underwent EVT due to BAO between December 2019 and July 2023 was retrospectively analyzed. According to the time when the patients were admitted, study population were divided into weekdays day time group and nights/weekends group. In subgroup analysis, study cohort was divided into four groups, including weekdays day time group, weekdays night time group, weekend day time group, and weekend night time group. Good outcome was defined as an modified Rankin Scale score ≤3 at 90 days after EVT. Time metrics [e.g. onset-to-door time (ODT), door-to puncture time (DPT)] and clinical outcomes were compared using appropriate statistical methods.Results: One hundred and eleven patients (88 male, mean age, 67.7±11.7 yeas) were included. Thirty-seven patients were treated during weekdays day time, while 74 patients were treated during nights or weekends time. There were no statistically significant differences on ODT (P=0.136), DPT (P=0.931) and also clinical outcomes (P=0.826) between two groups. Similarly, we also did not find any difference on the time metrics and clinical outcomes among four sub-groups (all P>0.05).This study did not reveal any influence of "weekend effect" on the time metrics and clinical outcomes in AIS patients who underwent EVT due to BAO at a comprehensive stroke center.